The prevalence of dementia in a Portuguese community sample: a 10/66 Dementia Research Group study - Manuel Gonçalves-Pereira (BMC Geriatrics, 2017)
Abstract Background Dementia imposes a high burden of disease worldwide. Recent epidemiological studies in European community samples are scarce. In Portugal, community prevalence data is very limited. The 10/66 Dementia Research Group (DRG) population-based research programmes are focused in low and middle income countries, where the assessments proved to be culture and education fair. We applied the 10/66 DRG prevalence survey methodology in Portugal, where levels of illiteracy in older populations are still high. Methods A cross-sectional comprehensive one-phase survey was conducted of all residents aged 65 and over of two geographically defined catchment areas in Southern Portugal (one urban and one rural site). Nursing home residents were not included in the present study. Standardized 10/66 DRG assessments include a cognitive module, an informant interview and the Geriatric Mental State-AGECAT, providing data on dementia diagnosis and subtypes, mental disorders including depression, physical health, anthropometry, demographics, disability/functioning, health service utilization, care arrangements and caregiver strain. Results We interviewed 1405 old age participants (mean age 74.9, SD = 6.7 years; 55.5% women) after 313 (18.2%) refusals to participate. The prevalence rate for dementia in community-dwellers was 9.23% (95% CI 7.80–10.90) using the 10/66 DRG algorithm and 3.65% (95% CI 2.97–4.97) using DSM-IV criteria. Pure Alzheimer’s disease was the most prevalent dementia subtype (41.9%). The prevalence of dementia was strongly age-dependent for both criteria, but there was no association with sex. Conclusions Dementia prevalence was higher than previously reported in Portugal. The discrepancy between prevalence according to the 10/66 DRG algorithm and the DSM-IV criteria is consistent with that observed in less developed countries; this suggests potential underestimation using the latter approach, although relative validity of these two approaches remains to be confirmed in the European context. We improved the evidence base to raise awareness and empower advocacy about dementia in Portugal, so that the complex needs of frail older people may be met in better ways.